Mapping the Financial Technology Industry in Indonesia - Renaldo, Nicholas; Junaedi, Achmad Tavip; Musa, Sulaiman; Wahid, Nabila; Cecilia, Cecilia (Journal of Applied Business and Technology, 2024)
This study aims to deepen the fintech landscape in Indonesia with focus on types of fintech, companies popular, and the role of fintech market aggregators. With internet penetration reached 67%, Indonesia became lush backdrop for fintech innovation, supported by regulation and proactive government to support the growth sector This. Methodology study combine study literature, studies cases, interviews with holder interests, research field, analysis statistics, SWOT analysis, surveys users, and analysis continuity. The literature review provides a base for understanding global fintech trends, interim studies case detail development leading fintech companies like My Capital, Friends Money, and Kredivo. Research result covers identification four main types of fintech in Indonesia: P2P Lending and Crowdfunding, Management Risk Investment, Payment-Clearing-Settlement, and Market Aggregator. Fintech market aggregators such as Cekaja.com, Cermati.com, and DuitPintar.com play role important in give information and comparison product finance to consumer. With results study This is expected can give understanding deep about the evolution of fintech in Indonesia, as well give base for policy public, developers business, and internal investors optimizing growth and inclusion finance in the digital era.